State Regulation of Organic Agriculture Development - POLUSHKINA, Tatyana Mihailovna; AKIMOVA, Yulia Alekseevna; KOCHETKOVA, Svetlana Andreevna (Journal of Environmental Management and Tourism; Vol 7 No 3 (2016): JEMT Volume VII Issue 3(15) Fall 2016, 2016)
The main goal of the research was to study and systemize measures of state regulation of the development of organic agriculture in Russia and abroad as well as to develop top-priority areas of its improvement. The Russian market of organic agricultural products has started its formation not long ago, and this area has not been enough studied. The article shows theoretical and methodological review of the references of native and foreign researchers, defines the vector of development of organic agriculture under contemporary terms and conditions of state regulation. Based on the conducted empiric research of maintaining and supporting organic agriculture in foreign countries for the period of 2010-2013, the advantages, principles and peculiarities of state support were revealed. The article defines the necessity to use foreign experience on the territory of Russia where almost half of agricultural products are produced in private subsidiary farms according to principles of farming that are close too organic. The analysis of the system of enactments in the area of regulating the development of organic agricultural production revealed the lack of the unified standard of producing and marking organic products in the country. Therefore, the authors stipulated the necessity to develop an accurate system of state regulation including: the creation of the regulatory and legal framework, national standards and marking; the formation of the culture of organics” consumption on the state level; the development of the Concept of organic agriculture development; the creation of the efficient system of state regulation and control over the development of organic agriculture in the Russian Federation. The implementation of the above measures will contribute to efficient development of the system of state regulation of organic productions taking into account new economic conditions.
Keywords: state; regulation; agriculture; organic farming; organic agriculture